2009
DOI: 10.5551/jat.e695
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Cofactor II is an Independent Protective Factor against Peripheral Arterial Disease in Elderly Subjects with Cardiovascular Risk Factors

Abstract: Aim: Heparin cofactor (HC ) specifically inactivates thrombin action at the injured vascular wall. We have reported that HC is a protective factor against coronary in-stent restenosis and carotid atherosclerosis; however, it is unclear whether there is any correlation between plasma HC levels and the development of peripheral arterial disease (PAD). Methods: Plasma HC activity and the ankle brachial pressure index (ABI) were determined in 494 elderly subjects with cardiovascular risk factors. PAD was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Recently, we have reported that plasma HCII activity is inversely correlated to the prevalence of peripheral arterial disease and that HCII is an independent inhibitory factor against peripheral arterial disease in elderly patients with cardiovascular risk factors (16). From those results, we hypothesized that HCII is involved in the process of angiogenesis in ischemic tissues.…”
Section: Heparin Cofactor II (Hcii)mentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, we have reported that plasma HCII activity is inversely correlated to the prevalence of peripheral arterial disease and that HCII is an independent inhibitory factor against peripheral arterial disease in elderly patients with cardiovascular risk factors (16). From those results, we hypothesized that HCII is involved in the process of angiogenesis in ischemic tissues.…”
Section: Heparin Cofactor II (Hcii)mentioning
confidence: 96%
“…We have shown pathophysiological roles of HCII action such as protective effects against cardiovascular remodeling (8,9,(12)(13)(14)16). In addition, Huang et al showed that plasma HCII activity is positively correlated with flow-mediated vasodilatation, a marker of endothelial function, suggesting that HCII increases NO bioavailability in humans (40).…”
Section: Patients and Animals With Peripheral Circulation Insufficienmentioning
confidence: 99%
“…ABI was measured using a method described elsewhere [22][23][24] . Briefly, the patient remained still in the supine position for 5 minutes, and a cuff for blood pressure measurement was then applied to both arms and legs.…”
Section: Measurement Of Transcutaneous Oxygen Tension (Tcpo2) and Ankmentioning
confidence: 99%
“…31 Because the endogenous protective factors against progression of PAD are still unknown, we also speculated that HCII plays a protective role against the development of PAD and measured plasma HCII activity and the ankle -brachial pressure index (ABI) in 494 Japanese elderly subjects with cardiovascular risk factors. 32 Diagnosis of PAD was made by ABI <0.9, and 62 subjects were determined as having PAD. Multivariate logistic regression analysis showed that age, current smoking, and the presence of diabetes mellitus were independently and positively associated with the prevalence of PAD.…”
Section: Padmentioning
confidence: 99%
“…Conversely, HCII was independently and negatively associated with the prevalence of PAD. 32 In addition, Schillinger et al 33 studied 63 consecutive patients with PAD who underwent femoropopliteal stent implantation after initial failure of plainballoon angioplasty. They measured plasma HCII activity in each patient before stenting and followed them for a median 10 months for the occurrence of the first in-stent restenosis.…”
Section: Padmentioning
confidence: 99%